Advances in electronics and electron physics - Morgan, B. L. (Brian Lealan), 1940-; Airey, R. W.; McMullan, D. (Advances in electronics and electron physics, 1976)
ADV ELECTRONC/ELECTRON PHYSICS V40B APL.